Youth, community and the struggle for social justice - Goddard, Tim (Routledge studies in crime, security and justice, 2018)
Introduction -- Background, context, and description of the social justice organizations -- Source reduction of delinquency and youth violence -- Navigating the dilemmas of funding and reporting -- Negotiating neoliberal governance and the political limits of community -- The promise and perils faced: grassroots mobilizing and the carceral state.